Statistics made simple for healthcare and social science professionals and students - Wong, Kam Cheong (Penerbit Universiti Putra Malaysia, 2006)
The fundamentals of statistics, sampling, types of data, levels of measurement and hypothesis testing are covered in Chapter 1, 2, and 3.Chapter 4 deals with the chi-square test, which can be applied for nominal (categorical) or ordinal data. Categorical data that are commonly collected in epidemiological studies to investigate relative risks and odds ratio are dealt with in Chapter 5. Statistical tools for handling and analyzing interval data are elaborated in Chapter 6 (t-test and Z-test), Chapter 7 (ANOVA) and Chapter 8 (Regression Analysis).